The Administrative Investigation into Disciplinary Offenses According to the Libyan Legal System (Journal of human and social sciences, 2025)
In this research, we studied a topicunder the title of "The Administrative Investigation into Disciplinary Offenses According to the Libyan Legal System." The reason for choosing this topic stems from its utmost importance within the framework of the public function in consideration that it constitutes the first effective procedures taken to address the administrative violations and prohibitions when they occur. It serves also as a guarantee for disciplining the accused employee. We addressed itsrecitals and details according to a three-part plan divided into sections, demands and branches. Through this, we defined the investigation linguistically as ensuring the accuracy and truthfulness of the information. Terminologically, it is the initial procedure that begins with the stage of collecting evidences and proofs regarding the facts attributed to the employee to ascertain the extent of the truth and validity of the accusation. We had clarified its elements based on the authority overseeing it, namely the administrative authority with its ordinary and supreme disciplinary two councils which are competent in administrative violations and the administrative control authority represented by its financial council and its jurisdiction over financial violations. In the administrative investigation we also dealtwithits formal and substantive aspects, its objective, its controls amongst those related to the investigation itself such as writing and confidentiality and others concern the investigator himself such as integrity and trustworthiness. We concluded the research with explaining how to handle the investigation which can be either temporarily shelved by the reason of the unknown perpetrator or insufficient evidences or permanently due to several reasons detailed in the research contextsuch as prescription, death of the accused person, falsification of the facts, insignificance and others or referral shall be made to the administrative authority. We concluded our research with findings and recommendations fromwhich we concluded that the administrative investigation is a means for deterring the wrongdoing and at the same time a guarantee for the offending employee. Also, the penalty imposed by the investigating authority is merely a resulting effect of the employee's violation of his legally imposed duties according to the law. We recommended for developing the legal system in Libya, issue of discipline law, development of the law No. (12)  of 2010 on labor relations, enlightening the public employee of his rights, guarantees and duties and enlightening the rights claiming culture amongst the right to resort to jurisdiction for equity regarding any Administrative abuse which may come upon him, in observance of the administrative investigation essence and its goal in realization of  the balance between the requirements of the public utility progress and guarantees of the employee.
Keywords: Administrative Investigation; Disciplinary Offenses; Libyan Law; Public Employee; Disciplinary Guarantees